Special Features of a 24-hour Arterial Blood Pressure Profile in Healthy Children During the Period of Adaptation to Studying at Different School Types - I. N. Zakharova; T. M. Tvorogova; I. I. Pshenichnikova; M. A. Shkolnikova (Union of pediatricians of Russia, 2015)
Arterial hypertension in children is a serious socially important problem, because it holds a position within the top of cardiovascular diseases, beginning from the adolescent age. A timely start of preventive measures based on appropriate forecast assessment in children from risk groups will make it possible to reduce the disease burden in elder age groups. Research purpose. Based on comprehensive assessment of clinic-anamnestic, genealogic, psychologic data, peculiarities of daily profile of arterial tension in the course of adaptation to education in educational institutions, to characterize the markers and single out the factors associated with AT increase in children that are considered relatively healthy.Patients. On a voluntary basis, 199 children of 1-2 health groups were included in the research at the age of 10-12 years (11.3 ± 0.02 years) who had just started their education at a cadet educational institution or middle school. The children did not have any complaints by the time of the research, nor did they have the necessity of taking medicines which could have an effect on the cardiovascular system and acute infectious diseases during the previous month.Methods. The research was carried out during the period from September 2013 until May 2014 in 2 successive stages corresponding to the first and second academic terms. The examination included clinic-anamnestic and genealogic methods, anthropometry, three-fold measuring of arterial pressure by Korotkoff's method, 24-hour ECG and AP monitoring, monitoring of motion activity volume, study of general and school levels of anxiety and psychic tension, assessment of the vegetative nervous system condition, nature of exercise tolerance and volume of additional sports load, volume of additional academic load.Results. The most important predictors of AH development and elevated AP persistence in children aged 10-12 years of 1 and 2 health groups are: values of SAP and/or DAP 90 and 95 percentile taking into account sex, age and height at one-shot measurements, the presence of AH in relatives within the immediate family, excessive (over 75 percent for this age and height) body weight and high (over 96 bpm) values of average day-time heart rate following results of HM. The previous data concerning a quick enough adaptation of children to increased daily loads was confirmed, including an authentic increase of motion activity volume within educational programs of cadet educational institutions.